Rocker outsole shoe is not a threat to postural stability in patients with diabetic neuropathy. (April 2016) - Ghomian, Banafshe; Kamyab, Mojtaba; Jafari, Hassan; Khamseh, Mohammadebrahim; Healy, Aoife
Background: Rocker outsole shoes are commonly prescribed to patients with diabetic neuropathy to offload a particular area of the foot sole, thereby decreasing the risk of foot ulceration. Contrary to this, some evidence has reported a postural destabilising effect of these shoes in healthy adults. Objective: To explore the postural stability of patients with diabetic neuropathy who wear a rocker outsole shoe. Study design: Quasi-experimental. Method: In total, 17 patients with diabetic neuropathy (aged 49.29 ± 7.48 years; 7 female, 10 males) participated in this study. A Motor Control Test measuring centre of force displacement, response strength scale and response latency in medium and large perturbations was conducted using the EquiTest system to evaluate postural stability while wearing a baseline shoe (without a rocker outsole) or a rocker outsole shoe (with a toe-only rocker sole). Results: No significant difference was observed between the shoe conditions in centre of force displacement and response latency of the participants (p > 0.05). The results indicated a significant increase in the response strength scale of participants by the rocker outsole, for medium forward and backward and large forward perturbations ( p  = 0.014, p  = 0.001 and p  = 0.027, respectively). Conclusion: When the immediate effect is a concern, the rocker outsole shoe did not negatively affect postural stability in patients with diabetic neuropathy. Clinical relevance: This article will provide objective evidence about the effect of rocker outsole on postural balance in diabetic patients. In prescription of rocker outsole to prevent plantar ulceration of diabetic foot, immediate postural destabilising is not a concern.